THE INSURGENCY OF ADAT, AN IMPEDIMENT TO INDONESIA AS A COMMON PROJECT - Tirtosudarmo, Riwanto (KRITIS, 2021)
This article traces what is known as adatrechtpolitiek within the contexts of social unrest among the natives inspired by Islam. Adat is a form of identity politics from above and cannot be isolated from the colonial policy to contain the rise of political Islam. As adat posits exclusive and distinct characteristics it is problematic after independence to revive it for social engineering as Indonesia is a common project that is based on equality of its citizens. The main question is therefore whether or not the deployment of adat in the current political development will be an impediment for Indonesia as a common project. Using evidence from several adat communities, this article exposes the impasse of continuing adat politics as only masking real challenges confronted by contemporary Indonesian society. In the current rise of conservative Islam, rehearsing adat as identity politics is dangerous in promoting a divided society. Inclusive citizenship as an embodiment of a common project in which the right of individual and the right of community is accommodated should be the ultimate solution to eradicate inequality and to fulfill social justice.